2021
DOI: 10.21037/apm-21-3278
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of stroke complicated with hospital-acquired pneumonia: a systematic review and meta-analysis of cohort studies

Abstract: Background: Hospital-acquired pneumonia (HAP) is a common type of nosocomial infection and a common complication experienced by stroke patients during hospitalization. HAP can aggravate patients' primary disease condition and lead to death. Clinically, a variety of factors may affect the occurrence of HAP in patients. In this study, we conducted a meta-analysis of the literature to investigate the risk factors of stroke with HAP for clinical reference. Methods:The PubMed, Medline, Embase and Cochrane Library d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Studies of SAP by Chen et al, Xu et al, and Guo et al also found K . pneumoniae to be the most common pathogenic organism [ 67 , 93 , 96 ], and this bacterium has also been linked with aspiration pneumonia [ 11 , 97 100 ]. For HAP, the most common causative organisms were carbapenem-resistant A .…”
Section: Discussionmentioning
confidence: 99%
“…Studies of SAP by Chen et al, Xu et al, and Guo et al also found K . pneumoniae to be the most common pathogenic organism [ 67 , 93 , 96 ], and this bacterium has also been linked with aspiration pneumonia [ 11 , 97 100 ]. For HAP, the most common causative organisms were carbapenem-resistant A .…”
Section: Discussionmentioning
confidence: 99%
“…Third, the severity of stroke is a risk factor for infection after stroke. 28 In patients with NIHSS score >15, Thus, patients who have a severe stroke and are at high risk of infection could be considered for prophylactic antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the effects of different administration times, we performed a subgroup analysis and found a decreasing trend in pneumonia in patients with early prophylactic use of antibiotics within 24 h after admission (RR 0.81 [95% CI: 0.62–1.07], I 2 = 0%) as compared with those using prophylactic use of antibiotics within 48 h after admission (RR 0.94 [95% CI: 0.79–1.11], I 2 = 0%). Third, the severity of stroke is a risk factor for infection after stroke 28 . In patients with NIHSS score >15, prophylactic antibiotics had a trend to reduce mortality rate (RR 0.63 [95% CI: 0.28–1.41]) and the incidence of pneumonia (RR 0.63 [95% CI: 0.28–1.41]), though there is no significant statistical difference.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the severity of stroke is a risk factor for infection after stroke. 27 Thus, patients with severe stroke who are at high risk for infection should be considered for prophylactic antibiotics. However, an RCT with a large sample size included in our meta-analysis involved patients with mild stroke, and the average hospital stay of patients was only 6.35 days.…”
Section: Discussionmentioning
confidence: 99%